Evaluation of Predictor Factors of Non-Diabetic Nephropathy in Diabetic Patient’s Biopsy Specimen in Labbafinejad Hospital - Samavat, Shiva; Dalili, Nooshin; Fatemizadeh, Somaye; Farhangparvar, Ali (Student Research in Translational Medicine, 2025)
Background and Aim: Nephropathy is one of the major complications in diabetic patients that causes high mortality worldwide. In diabetic patients, differentiating non-diabetic nephropathy from diabetic nephropathy is clinically essential in treating patients. The present study aimed to examine clinical, laboratory, demographic variables and their relationship with the type of non-diabetic nephropathy in diabetic patients. Methods: Clinical, demographic and laboratory data of 104 diabetic patients who underwent renal biopsy in Labbafinejad Hospital in Tehran in 2009-2010 were assessed. Patients were categorized into two groups based on the type of nephropathy (whether diabetic or non-diabetic). The recorded data were statistically compared between the two groups at the time of kidney biopsy and six months later. Results: In this study, 104 patients were studied. The mean age of patients was 57.2 ± 13.4 years, and 50% of patients were male. Shorter duration of diabetes, no insulin use, renal failure, higher mean arterial pressure, smaller kidneys, lack of diabetic retinopathy, lower GFR and higher serum creatinine in patients with diabetic nephropathy were identical with non-diabetic nephropathy group (in all cases) (P < 0.05). Conclusion: The need for kidney biopsy in diabetic patients can be determined with acceptable accuracy using the mentioned demographic, clinical, imaging and laboratory data. This study showed that the six-month GFR index could be used as a prognostic marker in patients.